Insight on the cellular and molecular basis of blood vessel formation: A specific focus on tumor targets and therapy. Issue 1 (8th February 2023) - Stephen, Nimish Mol; Deepika, Udayawara Rudresh; Maradagi, Tehreem; Sugawara, Tatsuya; Hirata, Takashi; Ganesan, Ponesakki
Abstract: The cellular and molecular switches that govern angiogenesis are considered therapeutic targets for several diseases like tumors and atherosclerosis. Thus, understanding the detailed molecular mechanisms underlying the formation of the new blood vessel is essential for developing novel therapeutic strategies. The formation of a new blood vessel (angiogenesis) is tightly regulated by balancing pro‐ and antiangiogenic molecules. Dysregulated angiogenesis contributes to the pathogenicity of several diseases, including tumors associated with uncontrolled vessel growth. Experimental and clinical studies emphasize that angiogenesis is a critical step for the transition of the tumor to a life‐threatening malignancy. In recent years, angiogenesis has been targeted as one of the primary therapeutic goals for treating tumors, and rapid progress has been made by modulating its molecular regulators. Hence, the mechanisms of how blood vessel formation occurs could provide molecular insight into future angiogenic therapy. This review summarizes briefly the molecular players of blood vessel formation comprising vasculogenesis and angiogenesis and their role in tumor progression alongside antiangiogenic therapy. Abstract : The cellular and molecular switches of vasculogenesis and angiogenesis are highlighted. The molecular players of tumor angiogenesis are enumerated. Tumor angiogenic therapy and future antitumor approaches are outlined.